PENGARUH REPUTASI KAP, OPINI AUDIT, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Pertambangan Sub Sektor Batu Bara Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Muhammad Bayu Indra Permana; Andri Syahputra (Journal of Research and Publication Innovation, 2024)
This research aims to test and obtain empirical evidence regarding the influence of KAP Reputation, Audit Opinion and Financial Distress on Audit Delay with the object of coal sub-sector mining companies listed on the BEI in 2019-2023. This type of research uses quantitative, sampling techniques using purposive sampling techniques. The population used in this research was 26 companies with a selected sample of 21 companies with a total sample of 105 data. The analysis technique used in this research is multiple linear regression, assisted by using the E-views version 10 application. The research results are simultaneously Fcount > Ftable (6.535588 > 2.69), with a significant value of 0.000439 < 0.05, which means that KAP reputation, audit opinion and financial distress together influence audit delay. The partial research results show a t-count value of 3.402240 > t-table value of 1.98373, so it can be said that KAP reputation has an influence on audit delay. The partial research results show that the t-count value is 1.581269 < t-table value 1.98373, so it can be said that audit opinion has no effect on audit delay. The partial research results show that the calculated t value is 0.945913 <1.98373 t table value so it can be said that financial distress has no effect on audit delay.